2015
DOI: 10.56748/ejse.141921
|View full text |Cite
|
Sign up to set email alerts
|

Damage Identification of a Concrete Arch Beam Based on Frequency Response Functions and Artificial Neural Networks

Abstract: This paper presents a vibration-based structural health monitoring (SHM) technique for the identification of damage in a concrete arch beam replica section of the Sydney Harbour Bridge. The proposed technique uses residual frequency response functions (FRFs) combined with principal component analysis (PCA) to form a damage specific feature (DSF) that is used as an input parameter to artificial neural networks (ANNs). Extensive laboratory testing and numerical modelling are undertaken to validate the method. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, to tackle the challenges of incomplete and imprecise data, Mehrjoo et al [269] discussed the numerical analyses of an ANN-based method for the intensity estimation of damage in truss bridge joints. Favarelli et al [270], and Weinsteinet al [271], Nguyen et al [272], and Jayasundara [273], employed ANN-based anomaly detection with bridge vibrational data, and Xu et al [274] developed an ANN-based two-step algorithm for vibration-based damage identification (VBDI) applied on the Crowchild Bridge located in Alberta, Canada. Eftekhar et al [275] integrated ANNs with proper orthogonal decomposition (POD) and subspace-based damage indicators, respectively.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to tackle the challenges of incomplete and imprecise data, Mehrjoo et al [269] discussed the numerical analyses of an ANN-based method for the intensity estimation of damage in truss bridge joints. Favarelli et al [270], and Weinsteinet al [271], Nguyen et al [272], and Jayasundara [273], employed ANN-based anomaly detection with bridge vibrational data, and Xu et al [274] developed an ANN-based two-step algorithm for vibration-based damage identification (VBDI) applied on the Crowchild Bridge located in Alberta, Canada. Eftekhar et al [275] integrated ANNs with proper orthogonal decomposition (POD) and subspace-based damage indicators, respectively.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Eftekhar et al [275] integrated ANNs with proper orthogonal decomposition (POD) and subspace-based damage indicators, respectively. Nguyen et al [276] leveraged ANNs with residual FRFs and PCA for SHM of a concrete arch beam replica. Tran [277] also provided a thesis focused on the damage detection accuracy of ANN-based methods.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…In recent years, several authors (e.g., Jin et. al 2016, Onur and Abdeljaber 2015, Nguyen et. al 2015 have concluded that structural damage detection is a problem of pattern recognition, in which a classification is made as function of physical properties of a system.…”
Section: Introductionmentioning
confidence: 98%
“…utilized the PINN to effectively predict the water flow in unsaturated soils governed by the intricate Richardson‐Richards equation. All these studies highlight the potential of PINN in solving pile‐related emerging concerns such as damage detection, 32,33 reliability assessment, 9,10 and design optimization 11–13 . Even though preliminary investigation of PINN for pile assessment has been conducted, 34 it does not comprehensively capture all the crucial factor for pile response, such as geometric nonlinearity, impeding its application.…”
Section: Introductionmentioning
confidence: 99%